What is responsible for the strong observed asymmetry in teleconnections between El Niño and La Niña?. Issue 3 (11th February 2014) - Zhang, Tao; Perlwitz, Judith; Hoerling, Martin P.
Abstract A large asymmetric component (El Niño + La Niña) of El Niño–Southern Oscillation (ENSO)‐related teleconnections over North America is found during 1984–2009 that is comparable in strength to the commonly studied symmetric component (El Niño − La Niña). Climate reforecasts spanning this period are diagnosed in order to understand the processes responsible for the observed asymmetry. It is confirmed that an asymmetric component is indeed a fundamental property of atmospheric responses to recent ENSO forcing. Each and every composite of a 16‐member reforecast ensemble has appreciable asymmetry in tropical Pacific rainfall, upper tropospheric Pacific‐North American circulation patterns, and contiguous U.S. surface temperatures. There is considerable sampling variability in the magnitude of this asymmetric component among individual reforecast composites. We argue therefore that the true sea surface temperature boundary‐forced signal of ENSO teleconnections is likely composed of a symmetric component having greater magnitude than its asymmetric component, though the latter is an important property of how ENSO affects North American climate.